Sistema de apoio à decisão para utilização no agronegócio (SADA): telemetria e tratamento de dados de desempenho de máquina de colheita - Sichonany, Oni Reasilvia de Almeida Oliveira (2011)
To obtain higher profitability in farms, it is essential to proper management of the operations performed, caused by concern over the operational cost of the machines used, which represents a high percentage compared to total costs of operation and can be up to forty percent. This cost can be reduced if the use of machinery is optimized, improving performance and efficiency operational, which is possible by monitoring the machine during its activity in the field. The information for the control can be obtained through the network of sensors and / or Global Positioning System (GPS), which detect and report any physical characteristic of the environment. The telemetry transmission allows instant communication with remote areas through wireless network, with a central information collection. Therefore, the purpose of this study is to develop a prototype Decision Support System for use in Agribusiness (SADA), which allows the manager of agribusiness to the operational control of the agricultural machine. The system was tested in a real harvesting operations in rice and soybean and the harvester machine used was a Massey Ferguson brand, 5650. The tests showed that the redundancy was effective and ensured the transmission through the exchange of technology without degradation of time, since in case of disconnection of the GSM modem, the system takes 30 milliseconds to connect to Xtend and send the data. The system T-SADA has achieved its objectives, secured transmission of data with fault tolerance and redundantly in remote locations and different relief as plain (without obstacles) and small elevations (with some obstacles, hills). The implementation of SADA allowed the confirmation of the hypothesis that the telemetry (T-SADA), combined with a management system (G-SADA), lets you monitor the performance of agricultural machinery on field operations and alert the wrong done.